Strategy As Leadership : facing adaptive challenges in organizations - Vassolo, Roberto; Weisz, Natalia (Stanford, California: Stanford Business Books, 2022)
"The authors argue that changes often are predictable, it does not follow that the solutions to these changes come pre-defined. Instead, companies will need to work hard to find the most appropriate and contextually relevant answers. The sooner they can identify and understand the dynamics, the more rapid and effective can be their adaptation and their allocation of resources to the losses that will occur. They focus on how firms faced with changes that can bring about a shift in strategic priorities often fail in what are fairly predictable environments. It's a topic the authors know well from both their consultancy and exec. education courses, as well as research as academics. The authors, both at a major business school in Latin America, have strong backgrounds in management studies, (Purdue and Harvard), and have a strong presence in Latin America through their teaching at IAE Business School in Argentina. Their consultancy work with multinational companies is also substantial. The book will find a large professional audience in business across senior management teams, executives in top leadership roles, and business consultants in strategic planning, change management, and leadership"--
The developmental challenge -- Navigating the developmental challenge -- Preparing for the developmental challenge -- The creative challenge -- Navigating the creative challenge -- The emergency challenge -- Navigating the emergency challenge -- The structural challenge -- Navigating the structural challenge -- Leading through concurrent challenges -- The future of strategy as leadership.
Includes bibliographical references (pages 189-195) and index.
Keywords: Strategic planning; Leadership; Organizational change